From psychological wellbeing to distress: the role of psychological counseling interventions in university students - Craig, Francesco; Colella, Gianluca Mariano; Tenuta, Flaviana; Mauti, Martina; Gravina, Antonio; Calomino, Maria Luigia; Plastina, Roberta; Polito, Alberto; Costabile, Angela (Frontiers in Psychology, 2025)
IntroductionUniversity students encounter specific psychosocial challenges contributing to increasing psychological distress. The dual continua model posits that psychological wellbeing and distress are separate yet interrelated aspects of mental health. This study examines the relationships between psychological wellbeing, academic engagement, and mental distress in students seeking support from a University Psychological Counseling Service and evaluates the effectiveness of psychological counseling interventions in improving wellbeing and reducing distress.MethodsA mixed-method approach was adopted, incorporating both cross-sectional and longitudinal analyses. A total of 246 students completed self-report measures such as the Ryff's Psychological Wellbeing Scale, the SInAPSi Academic Engagement Scale, and the Clinical Outcomes in Routine Evaluation. For the longitudinal component, 90 students were assessed before (T0) and after (T1) six counseling sessions. Multiple regression and mediation analyses explored predictors of distress, while paired t-tests evaluated intervention outcomes.ResultsSelf-Acceptance (p < 0.001) and Environmental Mastery (p = 0.037) dimensions significantly predicted lower psychological distress. Academic engagement did not mediate the relationship between wellbeing and distress. Post-intervention, psychological distress decreased significantly (p < 0.001), with 56.7% of students falling over the clinical distress cut-off at T1 compared to 84.4% at T0. The Autonomy (p = 0.03) and Self-Acceptance (p = 0.002) dimensions showed significant post-intervention improvements. The current study emphasizes that mental health is a dynamic, multidimensional construct, including both psychological distress and wellbeing. Universities should integrate positive psychology into curricula and expand psychological counseling services to provide proactive support, focusing on resilience, stress management, and emotional regulation.